Application of an Imaging-Based Sum Score for Cerebral Amyloid Angiopathy to the General Population: Risk of Major Neurological Diseases and Mortality - Yilmaz, Pinar; Ikram, Mohammad Arfan; Ikram, Mohammad Kamran; Niessen, Wiro J.; Viswanathan, Anand; Charidimou, Andreas; Vernooij, Meike W. (Frontiers in Neurology, 2019)
Objective: To assess the relation between a sum score of imaging markers indicative of cerebral amyloid angiopathy (CAA) and cognitive impairment, stroke, dementia, and mortality in a general population. Methods: 1622 stroke-free and dementia-free participants of the population-based Rotterdam Study (mean age 73.1 years, 54.3% women) underwent brain MRI (1.5 tesla) in 2005–2011 and were followed for stroke, dementia and death until 2016–2017. Four MRI markers (strictly lobar cerebral microbleeds, cortical superficial siderosis, centrum semiovale perivascular spaces, and white matter hyperintensities) were combined to construct the CAA sum score, ranging from 0 to 4. Neuropsychological testing measured during the research visit closest to scan date were used to assess general cognitive function and cognitive domains. The associations of the CAA sum score with cognition cross-sectionally and with stroke, dementia, and mortality longitudinally were determined using linear regression and Cox proportional hazard modeling adjusted for age, sex, hypertension, cholesterol, lipid lowering medication, atrial fibrillation, antithrombotic medication and APOE-ε2/ε4 carriership. Additionally, we accounted for competing risks of death due to other causes for stroke and dementia, and calculated absolute risk estimates. Results: During a mean follow-up of 7.2 years, 62 participants suffered a stroke, 77 developed dementia and 298 died. Participants with a CAA score of 1 showed a lower Mini-Mental-State-Exam (fully-adjusted mean difference -0.21, 95% CI (-0.42¬¬–0.00) compared to a score of 0. In general, for increased CAA scores we saw a lower g-factor. The age and sex-adjusted hazard ratios (HRs) per point increase of the CAA score were 1.41 for stroke (95% CI, 0.99–2.00), 1.19 for dementia (95% CI , 0.86–1.65), and 1.26 for mortality (95% CI, 1.07–1.48). The results for dementia and stroke risk did not differ after correcting for the competing risk of death. For all outcomes, higher CAA scores showed higher absolute risk estimates over ten years. Conclusions: Our results suggest that in this community-dwelling population, a higher CAA score is related to cognitive impairment and a higher risk of stroke, dementia, and death. The composite CAA score can be used to practically quantify the severity of vascular brain injury.